2004
DOI: 10.1242/dev.01529
|View full text |Cite
|
Sign up to set email alerts
|

Defective paracrine signalling by TGFβ in yolk sac vasculature of endoglin mutant mice: a paradigm for hereditary haemorrhagic telangiectasia

Abstract: Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant disorder in humans that is characterised by multisystemic vascular dyplasia and recurrent haemorrhage. Germline mutations in one of two different genes,endoglin or ALK1 can cause HHT. Both are members of the transforming growth factor (TGF) β receptor family of proteins, and are expressed primarily on the surface of endothelial cells (ECs). Mice that lack endoglin or activin receptor like kinase (ALK) 1 die at mid-gestation as a result of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 62 publications
5
115
1
Order By: Relevance
“… HHT mutations (endoglin and ALK-1) impair recruitment of mural cells to vessels, 160,164 at least in part via reduced endothelial cell secretion of TGF-ß1 168,169 and/or reduced TGF-ß1 induced responses. 160,168 Endogenous Smad phosphorylation in mural cells is reduced, 168 29,173 Support for a fundamental role for aberrant angiogenesis and reactive oxygen species in HHT disease pathogenesis is accumulating in man, with case reports and small series suggesting that anti-angiogenic and anti-oxidant strategies may be of therapeutic benefit in HHT (see Sections 4 and 5 below).…”
Section: 2d) Generation Of Abnormal Vessels In Hhtmentioning
confidence: 99%
See 1 more Smart Citation
“… HHT mutations (endoglin and ALK-1) impair recruitment of mural cells to vessels, 160,164 at least in part via reduced endothelial cell secretion of TGF-ß1 168,169 and/or reduced TGF-ß1 induced responses. 160,168 Endogenous Smad phosphorylation in mural cells is reduced, 168 29,173 Support for a fundamental role for aberrant angiogenesis and reactive oxygen species in HHT disease pathogenesis is accumulating in man, with case reports and small series suggesting that anti-angiogenic and anti-oxidant strategies may be of therapeutic benefit in HHT (see Sections 4 and 5 below).…”
Section: 2d) Generation Of Abnormal Vessels In Hhtmentioning
confidence: 99%
“…160,168 Endogenous Smad phosphorylation in mural cells is reduced, 168 29,173 Support for a fundamental role for aberrant angiogenesis and reactive oxygen species in HHT disease pathogenesis is accumulating in man, with case reports and small series suggesting that anti-angiogenic and anti-oxidant strategies may be of therapeutic benefit in HHT (see Sections 4 and 5 below).…”
Section: 2d) Generation Of Abnormal Vessels In Hhtmentioning
confidence: 99%
“…TGF-b signaling plays an important role during vascular development and is known to maintain proper endothelial pericyte/ VSM cell interactions. TGF-b signaling in endothelial cells further drives the expression, synthesis, and release of TGF-b to nearby VSM cells to influence their differentiation (Carvalho et al, 2004;Wurdak et al, 2005). Studies suggest the importance of juxtaposed intercellular communication between endothelial cells and pericytes/ VSM cells for activation of the TGF-b pathway (Antonelli-Orlidge et al, 1989;Sato et al, 1990).…”
Section: Pericyte/vsm-endothelial Cell Interactions In the Tumor Micrmentioning
confidence: 99%
“…The importance of TGF-b signaling in the cardiovascular system is underlined by the observation that genetic deletion of several TGF-b family members, their receptors, or downstream signaling molecules results in death of the mutants because of severe defects in the yolk sac vasculature [29]. In this study, we have demonstrated that: (a) EC gene expression is diminished and TGF-bI/ TGF-b1R expression is upregulated in isolated islets maintained in culture; (b) islets contain two distinct populations of cells expressing the TGF-b accessory receptor endoglin, one of which coexpresses the EC marker CD31 in situ; (c) an endoglin-positive, MSC population expanded from human islets disrupts the proangiogenic properties of microvascular ECs and inhibits EC survival in vitro; these changes are associated with increased Smad2 phosphorylation, and (d) pharmacological inhibition of TbRI/ ALK5 improves EC survival in cultured islets and reduces the detrimental effects of MSCs on cocultured ECs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies in genetically modified mice revealed a TGF-b-mediated autoregulatory loop between ECs and MSCs, such that disrupted TGFb signaling in ECs impaired TGFb-driven ALK5 signaling in adjacent mesenchymal cells, inhibiting their differentiation into vascular smooth muscle cells and their association with developing endothelial tubes [29]. Also, coculture of bone marrow-derived MSCs with adult ECs on Matrigel causes EC cytotoxicity, resulting in capillary network breakdown [51].…”
Section: Discussionmentioning
confidence: 99%